GOOD CORPORATE GOVERNANCE (GCG) AND SALES GROWTH ON FINANCIAL PERFORMANCE THAT IMPACT COMPANY VALUE FOR MINING SECTOR COMPANIES - Azharudin; Rangkuti, Zulkifli; Hanaffy, Jamal (Jurnal Manajemen Bisnis Dan Organisasi, 2025)
This study aims to analyze the influence of good corporate governance (GCG) and sales growth on financial performance and firm value, including the role of financial performance as a mediating variable. The method used is path analysis with the help of SPSS 29. The results show that GCG and sales growth have a significant effect on financial performance with a contribution of 11.2%. Furthermore, GCG and sales growth also have a significant effect on firm value, while financial performance has no significant effect on firm value. Simultaneously, the three independent variables contribute 22.3% to firm value, while the remainder is influenced by other factors outside this study.